2023
DOI: 10.1097/mao.0000000000003985
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Socioeconomic Barriers to Cochlear Implantation

Rachel C. Greiner,
Jay T. Rubinstein,
Gavriel D. Kohlberg

Abstract: Objective To explore socioeconomic disparities in cochlear implant evaluation (CIE) referrals and cochlear implantation. Study Design Retrospective chart review. Setting Tertiary referral academic center. Methods Adult patients (n = 271) with an audiogram performed between 2015 and 2019 with a pure-tone average of at least 60 dB and word recognition score of 60% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…It is noted that while our data suggested that not having English as a first language did not significantly impact the discussion of cochlear implants, it did correlate with reduced referral rates. This is consistent with a study from the USA which revealed that non-English speaking patients received fewer referrals compared to English-speaking patients [ 19 ]. This may suggest difficulties in adequately explaining cochlear implantation as an option or cultural differences in approaching hearing loss treatment.…”
Section: Discussionsupporting
confidence: 92%
“…It is noted that while our data suggested that not having English as a first language did not significantly impact the discussion of cochlear implants, it did correlate with reduced referral rates. This is consistent with a study from the USA which revealed that non-English speaking patients received fewer referrals compared to English-speaking patients [ 19 ]. This may suggest difficulties in adequately explaining cochlear implantation as an option or cultural differences in approaching hearing loss treatment.…”
Section: Discussionsupporting
confidence: 92%